2009
DOI: 10.3897/zookeys.31.131
|View full text |Cite
|
Sign up to set email alerts
|

A new species of tooth-carp, Aphanius mesopotamicus, from Iran and Iraq (Actinopterygii, Cyprinodontidae)

Abstract: A new species of tooth-carp, Aphanius mesopotamicus (Cyprinodontidae), is described from southern Mesopotamia in Iran and Iraq. It is distinguished from related species by pigmentation (males have clear margins to the unpaired fi ns, no bars on the caudal fi n and 10-15 clearly defi ned fl ank bars; females bear irregular blotches or spots on the fl ank), distribution, and a suite of morphometric and meristic characters in multivariate space (pectoral fi n rays, caudal peduncle length, scales to pelvic fi n an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 797 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…mesopotamicus males from males of A . sophiae (Coad, ); the caudal peduncle length and numbers of lateral and caudal peduncle scales separate Aphanius arakensis Teimori, Esmaeili, Gholami, Zarei & Reichenbacher 2012 from other inland species of Aphanius (Teimori et al , ) and the numbers of lateral‐scale series are useful taxonomic criteria for the discrimination of A . vladykovi from Aphanius isfahanensis Hrbek, Keivany & Coad 2006, A .…”
Section: Discussionmentioning
confidence: 99%
“…mesopotamicus males from males of A . sophiae (Coad, ); the caudal peduncle length and numbers of lateral and caudal peduncle scales separate Aphanius arakensis Teimori, Esmaeili, Gholami, Zarei & Reichenbacher 2012 from other inland species of Aphanius (Teimori et al , ) and the numbers of lateral‐scale series are useful taxonomic criteria for the discrimination of A . vladykovi from Aphanius isfahanensis Hrbek, Keivany & Coad 2006, A .…”
Section: Discussionmentioning
confidence: 99%
“…: GenBank ‐82; A. vladykovi Coad, 1988: GenBank , and ; A. isfahanensis Hrbek et al. : GenBank and ‐89; A. mesopotamicus Coad : GenBank ; A. fasciatus (Valenciennes, in Humboldt and Valenciennes 1821): GenBank ; A. iberus (Valenciennes in Cuvier & Valenciennes 1846): GenBank ; Fundulopanchax sjostedti (Lönnberg, 1895): GenBank ; Epiplatys infrafasciatus (Günther, 1866): GenBank ; Aphyosemion polli Radda & Pürzl, 1987: GenBank .…”
Section: Methodsmentioning
confidence: 99%
“…They were commonly identified as Aphanius sophiae (Heckel, 1849) (Coad and Abdoli 2000; Kamal et al 2009); however, it was shown that the true Aphanius sophiae is restricted to the endorheic Kor River basin near Shiraz (Fars Province) (Coad 2009; Esmaeili et al 2012). This study describes a newly discovered Aphanius population from the Namak Lake basin in northern central Iran (Fig.…”
Section: Introductionmentioning
confidence: 99%